Biochemical characterization of TASSELSEED 2, an essential plant short-chain dehydrogenase/reductase with broad spectrum activities. - Wu, X; Knapp, S; Stamp, A; Stammers, D; Jörnvall, H; Dellaporta, S; Oppermann, U (2007)
The development of unisexual flowers in maize and other plants proceeds through selective elimination of floral organs in an initially bisexual floral meristem. The essential character of the tasselseed 2 gene (TS2) in this cell-death pathway has been established previously. Molecular cloning of TS2 reveals membership to the evolutionarily conserved superfamily of short-chain dehydrogenases/reductases, but its substrate specificity remained unknown. Recombinant TS2 protein was produced in Escherichia coli, and purified to apparent homogeneity. Analytical ultracentrifugation and gel filtration experiments show that TS2 is a tetrameric enzyme. Thermal denaturation followed by circular dichroism spectroscopy reveals that TS2 binds NAD(H) and NAD(P)(H). Substrate screening demonstrates that TS2 converts steroids with specificities found at positions 3 and 17, and several dicarbonyl and quinone compounds, thus establishing TS2 as a plant 3beta/17beta-hydroxysteroid dehydrogenase and carbonyl/quinone reductase. Taken together, the genetic data and the substrate specificities determined suggest that TS2 converts specific plant compounds and acts as a prereceptor control mechanism, in a manner similar to that of mammalian hydroxysteroid dehydrogenases.